The Effect of Using Free Talk Worksheets from English Planet’s Program on Speaking Achievement at the Tenth Grade Students of Vocational High School Plus Almaarif Singosari - Muhammad Yasminto (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2019)
This study investigated speaking achievement using free talk worksheets from English planet’s program at the tenth grade students of vocational high school plus Almaarif Singosari. Designed used in this study was true experimental research conducted with one experimental group taught using free talk worksheets from English planet’s program and control group without free talk worksheet from English planet’s program. To collect the data, the researcher used speaking post-test in oral test form. In analyzing the data, the researcher used IBM spss statistic versions. 20 application of independent t.test to know the differences between experimental and control group. After applying the statistical computation, it was found that the mean score of experimental group (X) in post-test 3.078 with standard deviation 0.347 was higher than the mean score of control group (Y) in post-test 2.263 with standard deviation 0.417. So it can be concluded that students taught using free talk worksheets from English planet’s program achieve better than taught without free talk worksheets from English planet’s program.